PENGARUH KEBIJAKAN DIVIDEN PADA NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CSR DAN GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI - Dewi, Putu Riska Amanda; putri, I.G.A.M Asri Dwija (E-Jurnal Akuntansi, 2017)
The size of a Dividend Payout Ratio will affect  investment decisions of shareholder, on the other hand affect company's financial condition. Study aims to determine effect of dividend policy on Corporate Value with the disclosure of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) as moderating the Company listed on  Indonesia Stock Exchange (IDX) period 2012-2015. This study took data on IDX with a secondary data collection methods. The number of samples analyzed were 36 observations, and use data retrieval methods of research with purposive sampling technique. Data have been valid and reliable, meet test that is classic assumption test and analysis techniques MRA using SPSS.Results of study provide evidence: 1) dividend policy doesn’t affect value of company. 2) CSR moderating influence on the value of company's dividend policy, 3) GCG doesn’t moderate influence on the value of company's dividend policy.
Keywords: Dividend Policy, Firm Values, CSR, GCG